Hydraulic low-carbon concrete containing barium sulfate barite and application of hydraulic low-carbon concrete in nuclear protection engineering

By combining calcined activated barium sulfate barite powder and modified fibers, a low-carbon concrete was prepared, which solved the problem of insufficient radiation protection and durability of existing concrete in nuclear protection projects, and achieved high-performance low-carbon building materials.

CN120247510APending Publication Date: 2025-07-04BEIJING JIAHE RADIATION PROTECTION CONSTRUCTION ENGINEERING CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510389215.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-28
Publication Date
2025-07-04

AI Technical Summary

Technical Problem

In the fields of nuclear energy utilization, radioactive material treatment and nuclear medicine, existing concrete materials are difficult to meet high radiation protection performance, good permeability and durability at the same time. At the same time, there are problems of high energy consumption and carbon emissions, and cannot meet the requirements of low-carbon environmental protection.

Method used

The hydraulic low-carbon concrete containing barium sulfate barite powder, modified polypropylene fiber, industrial waste residue light aggregate, nanosilica and boron carbide powder are used to form a hydraulic low-carbon concrete containing barium sulfate barite through a specific preparation process to achieve multiple performance improvements.

Benefits of technology

It achieves high compressive strength, low dry density, excellent neutron shielding and gamma ray attenuation performance and low chloride ion diffusion, meets low carbon environmental protection requirements, and is suitable for nuclear reactor containment and nuclear medical protective walls.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120247510A_ABST
    Figure CN120247510A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of light low-carbon concrete, and discloses hydraulic low-carbon concrete containing barium sulfate barite as well as a preparation method and application of the hydraulic low-carbon concrete. The concrete is prepared from 42.5-grade Portland cement, barium sulfate barite powder, modified polypropylene fiber, industrial waste residue lightweight aggregate, boron carbide powder, nano silicon dioxide, a polycarboxylate superplasticizer, a composite exciting agent and water according to specific parts by weight. Wherein the barium sulfate barite powder is subjected to graded proportioning and calcination activation, the modified polypropylene fiber is treated by plasma and a silane coupling agent, the industrial waste residue lightweight aggregate is formed by compounding fly ash ceramsite and steel slag microbeads, and the composite exciting agent is composed of specific components. The concrete is high in compressive strength, low in dry density, excellent in neutron shielding and gamma ray attenuation performance and low in chloride ion diffusion coefficient. The preparation method comprises the steps of premixing modification, gradient stirring, vibration compaction and steam curing. The concrete is suitable for construction of a nuclear reactor containment, a radioactive waste repository and a nuclear medicine protection wall.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of lightweight low-carbon hydraulic concrete, and discloses a hydraulic low-carbon concrete containing barite barium sulfate, its preparation method and application. Background Art

[0002] In the fields of nuclear energy utilization, radioactive substance treatment, nuclear medicine, and engineering related to fresh water environments, the requirements for building materials are extremely stringent. These fields not only require materials to have conventional structural strength properties, but also need to possess good neutron shielding, γ-ray attenuation, chloride ion penetration resistance, etc., in order to ensure personnel safety, environmental stability, and the durability of engineering facilities.

[0003] Existing concrete materials have obvious deficiencies in meeting these special requirements. In terms of radiation protection, ordinary concrete has weak neutron shielding and γ-ray attenuation capabilities, making it difficult to meet the high requirements for radiation protection in nuclear facilities, nuclear medicine protection sites, etc., and unable to provide reliable radiation shielding for personnel and equipment. In fresh water environments, although the chloride ion concentration is relatively low, long-term water erosion and other possible corrosive substances will still damage the concrete structure. Traditional concrete has certain limitations in terms of impermeability and durability, and it is difficult to ensure stable performance during long-term use in fresh water environments.

[0004] In addition, with the enhancement of environmental awareness and the deepening of the concept of sustainable development, low-carbon environmental protection has become an important direction for the development of building materials. Some existing high-performance concretes, whether used for radiation protection or fresh water environmental engineering, often require the use of a large amount of high-energy-consuming materials and complex preparation processes, which do not meet the requirements of low-carbon development.

[0005] Although marine cement can be used in fresh water environments, it still has limitations in both radiation protection performance and low-carbon environmental protection. Therefore, it is of great practical significance to develop a new type of concrete material that not only has excellent radiation protection performance, good impermeability and durability, but also meets the requirements of low-carbon environmental protection, and is mainly used in projects such as fresh water nuclear protection. Summary of the Invention

[0006] In view of the above problems, the present invention provides a hydraulic low-carbon concrete containing barite barium sulfate and its application in nuclear protection projects.

[0007] The present invention includes the following technical solutions:

[0008] A hydraulic low-carbon concrete containing barite barium sulfate, which is composed of the following raw materials in parts by weight:

[0009] 200 - 300 parts of 42.5 grade portland cement, 150 - 250 parts of barite powder, 3 - 8 parts of modified polypropylene fiber, 80 - 120 parts of industrial waste light aggregate, 10 - 20 parts of boron carbide powder, 5 - 15 parts of nano-silica, 2 - 5 parts of polycarboxylate water reducer, 1 - 3 parts of composite activator, 80 - 120 parts of water;

[0010] The modified polypropylene fiber is treated by plasma surface treatment and silane coupling agent modification.

[0011] Furthermore, for the above hydraulic low-carbon concrete containing barite, the barite powder adopts a graded ratio combination: ultra-fine powder with a particle size ≤ 10μm accounts for 30% - 40%, fine powder with a particle size of 10 - 30μm accounts for 40% - 50%, medium-fine powder with a particle size of 30 - 50μm accounts for 20% - 30%, and is calcined and activated at 600 - 800°C.

[0012] Furthermore, for the above hydraulic low-carbon concrete containing barite, the modification treatment steps of the modified polypropylene fiber include:

[0013] (1) Low-temperature plasma treatment: Under an oxygen atmosphere, treat with a radio frequency power of 50 - 100W for 5 - 10 minutes;

[0014] (2) Silane coupling agent treatment: Immerse the plasma-treated fiber in a 1% - 3% KH-550 ethanol solution and ultrasonically treat at 60°C for 30 - 60 minutes;

[0015] (3) Heat treatment: Dry and cure at 120 - 150°C for 1 - 2 hours.

[0016] Furthermore, for the above hydraulic low-carbon concrete containing barite, the industrial waste light aggregate is a composite aggregate of fly ash ceramsite and steel slag microspheres, and the mass ratio of the two is 2:1 - 3:1. The ceramsite particle size is 3 - 8mm, and the bulk density is 600 - 800kg / m 3 , and the steel slag microsphere particle size is 0.5 - 2mm.

[0017] Furthermore, for the above hydraulic low-carbon concrete containing barite, the composite activator is composed of sulphoaluminate clinker, gypsum and lithium hydroxide according to a mass ratio of 5:3:1, and the specific surface area ≥ 450m 2 / kg.

[0018] Furthermore, for the above hydraulic low-carbon concrete containing barite, the nano-silica has a mesoporous structure, the pore diameter is 2 - 5nm, the specific surface area is 300 - 500m 2 / g, and the surface is modified by amino silane.

[0019] Furthermore, the above-mentioned hydraulic low-carbon concrete containing barite has a compressive strength ≥ 60 MPa and a dry density ≤ 2200 kg / m 3 , a neutron shielding rate ≥ 85%, 137 γ-ray attenuation coefficient ≥ 0.35 cm under the -1 Cs source condition, and a chloride ion diffusion coefficient ≤ 2.5×10 -12 m 2 / s.

[0020] The present invention also discloses a preparation method of the above-mentioned hydraulic low-carbon concrete, which is characterized by including the following steps:

[0021] (1) Premixing and modification: First, dry mix 42.5-grade portland cement, nano-silica, and 1 / 4 - 1 / 2 mass of barite powder of barium sulfate for 5 - 10 minutes;

[0022] (2) Gradient stirring: Add the remaining raw materials in three times, with an interval of 3 - 5 minutes each time;

[0023] (3) Vibration compaction: Use high-frequency vibration molding at 20 - 40 Hz;

[0024] (4) Steam curing: Cure at a constant temperature of 80 - 90 °C for 12 - 24 hours.

[0025] Furthermore, in the above-mentioned preparation method, in step (2), the specific parameters of the gradient stirring are: the stirring speed in the first stage is 60 - 80 rpm and the time is 3 min; the stirring speed in the second stage is 120 - 150 rpm and the time is 5 min; the stirring speed in the third stage is 60 - 80 rpm and the time is 2 min.

[0026] The present invention also discloses the application of the above-mentioned hydraulic low-carbon concrete in the construction of nuclear reactor containment vessels, radioactive waste repositories, or nuclear medicine protection walls.

[0027] Compared with the prior art, the present invention has the following prominent beneficial effects:

[0028] By using the barite powder of barium sulfate with graded ratio calcination activation (ultrafine powder with a particle size ≤ 10 μm accounting for 30% - 40%), polypropylene fibers modified by plasma and silane coupling agents, and industrial waste light aggregates composed of fly ash ceramsite and steel slag microspheres, and combining the synergistic effects of nano-silica and boron carbide, the present invention has achieved multiple technological breakthroughs. Specifically, the compressive strength ≥ 60 MPa (68.5 MPa in Example 2), the dry density ≤ 2200 kg / m 3 (14% lighter than traditional shielding concrete), the neutron shielding rate ≥ 85% (88.3% in Example 2), 137 γ-ray attenuation coefficient of -1(In Example 2, it reaches 0.38 cm -1 ), the chloride ion diffusion coefficient ≤ 2.5×10 -12 m 2 / s (in Example 2, it is 1.8×10 -12 m 2 / s). The comprehensive performance far exceeds that of ordinary concrete (for example, in Comparative Example 1, the compressive strength is only 42.3 MPa and the neutron shielding rate is 32.1%). At the same time, using 32% of industrial waste residue and a low-temperature calcination process at 800 °C, the carbon emission is reduced by 41% (280 kg / m 3 ). It has the characteristics of high radiation shielding, light weight and high strength, impermeability and durability, and low-carbon environmental protection, and is suitable for scenarios such as nuclear reactor containments and medical protection walls, filling the performance gap of traditional materials in nuclear protection projects. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 is the comparison of the compressive strength (MPa) of the concrete in the examples and comparative examples;

[0030] Figure 2 is the comparison of the dry density (kg / m 3 ) of the concrete in the examples and comparative examples;

[0031] Figure 3 is the comparison of the neutron shielding rate (%) of the concrete in the examples and comparative examples

[0032] Figure 4 is the γ attenuation coefficient (cm -1 ) of the concrete in the examples and comparative examples;

[0033] Figure 5 is the Cl⁻ diffusion coefficient (×10 -12 m 2 / s) of the concrete in the examples and comparative examples. DETAILED DESCRIPTION OF THE INVENTION

[0034] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.

[0035] Table 1 Experimental reagents

[0036]

[0037] Example 1

[0038] 1. Composition of raw materials (parts by weight):

[0039] Portland cement of grade 42.5: 200 parts

[0040] Barium sulfate barite powder: 150 parts (grading ratio: ≤10μm accounts for 30%, 10 - 30μm accounts for 50%, 30 - 50μm accounts for 20%)

[0041] Modified polypropylene fiber: 3 parts (treated by 50W plasma for 5 minutes + 1% KH - 550 treatment)

[0042] Industrial waste light aggregate: 80 parts (fly ash ceramsite: steel slag microbead = 2:1, ceramsite 3mm, microbead 0.5mm)

[0043] Boron carbide powder: 10 parts

[0044] Nano - silica: 5 parts (aminosilane modification, pore diameter 2nm, specific surface area 500m 2 / g)

[0045] Polycarboxylate water - reducing agent: 2 parts

[0046] Compound activator: 1 part (calcium sulfoaluminate clinker: gypsum: lithium hydroxide = 5:3:1)

[0047] Water: 80 parts

[0048] 2. Preparation method

[0049] 1) Premixing and modification: Cement, nano - SiO2 and 1 / 4 of the barite powder are dry - mixed for 5 minutes

[0050] 2) Gradient stirring:

[0051] The first stage (60rpm, 3min): Add the remaining barite powder and light aggregate

[0052] The second stage (120rpm, 5min): Add boron carbide, water - reducing agent, compound activator

[0053] The third stage (60rpm, 2min): Add modified fiber and water

[0054] 3) Vibration compaction: High - frequency vibration molding at 20Hz

[0055] 4) Steam curing: Constant - temperature curing at 80°C for 24 hours

[0056] Example 2

[0057] 1. Raw material composition (parts by weight):

[0058] Portland cement: 250 parts

[0059] Barite powder: 200 parts (grading ratio: ≤10μm accounts for 35%, 10 - 30μm accounts for 45%, 30 - 50μm accounts for 20%)

[0060] Modified polypropylene fiber: 5.5 parts (treated with 75W plasma for 7 minutes + 2% KH-550 treatment)

[0061] Lightweight aggregate of industrial waste residue: 100 parts (ceramsite: microbead = 2.5:1, ceramsite 5mm, microbead 1mm)

[0062] Boron carbide powder: 15 parts

[0063] Nano-SiO2: 10 parts (pore size 3nm, specific surface area 400m 2 / g)

[0064] Polycarboxylate superplasticizer: 3.5 parts

[0065] Compound activator: 2 parts

[0066] Water: 100 parts

[0067] 2. Preparation method:

[0068] The gradient stirring parameters are adjusted to: the first stage 80rpm / 3min, the second stage 150rpm / 5min, the third stage 80rpm / 2min, and the rest is the same as in Example 1.

[0069] Example 3

[0070] 1. Raw material composition (parts by weight):

[0071] Portland cement: 300 parts

[0072] Barite powder: 250 parts (grading ratio: ≤10μm accounts for 40%, 10-30μm accounts for 40%, 30-50μm accounts for 20%)

[0073] Modified polypropylene fiber: 8 parts (treated with 100W plasma for 10 minutes + 3% KH-550 treatment)

[0074] Lightweight aggregate of industrial waste residue: 120 parts (ceramsite: microbead = 3:1, ceramsite 8mm, microbead 2mm)

[0075] Boron carbide powder: 20 parts

[0076] Nano-SiO2: 15 parts (pore size 5nm, specific surface area 300m 2 / g)

[0077] Polycarboxylate superplasticizer: 5 parts

[0078] Compound activator: 3 parts

[0079] Water: 120 parts

[0080] 2. Preparation method: The vibration frequency is increased to 40 Hz, and steam curing is carried out at 90 °C for 12 hours. The rest is the same as in Example 2.

[0081] Comparative Examples 1-5

[0082] Set up comparative examples as shown in Table 2.

[0083] Table 2: Settings of Comparative Examples

[0084]

[0085] Test Example

[0086] Test Items and Standards

[0087] 1. Compressive strength: GB / T 50081-2019

[0088] Test object: Concrete cube specimens (150 mm × 150 mm × 150 mm)

[0089] Test steps:

[0090] Specimen preparation: Cast specimens according to the standard mix ratio and cure them in an environment of (20 ± 2) °C and relative humidity ≥ 95% for 28 days.

[0091] Loading equipment: Use a servo pressure testing machine with a range of 20% - 80% of the expected failure load.

[0092] Loading rate: Continuously and uniformly load at a rate of (0.5 ± 0.1) MPa / s until the specimen fails.

[0093] Result calculation: Compressive strength (F max is the maximum load, and A is the bearing area).

[0094] 2. Dry density: GB / T 11969-2020

[0095] Test object: Hardened concrete specimens (100 mm × 100 mm × 100 mm).

[0096] Test steps:

[0097] Specimen treatment: After curing, place the specimens in an oven at (105 ± 5) °C and dry them to a constant weight (the difference between two weighings ≤ 0.1%).

[0098] Mass measurement: Weigh the mass m after drying with an electronic balance with a precision of 0.1 g d (unit: g).

[0099] Volume measurement: Determine the volume V of the specimens by the drainage method (unit: cm 3 ).

[0100] Result calculation: Dry density (Unit: kg / m 3 )

[0101] 3. Neutron shielding rate (thermal neutron, 0.025 eV): GB / T 16140 - 2018

[0102] Test object: Concrete slab (thickness 100 mm, area 300 mm × 300 mm).

[0103] Test conditions:

[0104] Neutron source: 252 Cf spontaneous fission neutron source (average energy 2.13 MeV, thermal neutron flux 1×10 6 n / cm 2 ·s).

[0105] Detector: 3He proportional counter (placed 50 cm behind the specimen).

[0106] Test steps:

[0107] Background measurement: Measure the neutron count N0 without the specimen (for 10 min).

[0108] Shielding measurement: Measure the transmitted neutron count N after placing the specimen (for the same time).

[0109] Result calculation: Neutron shielding rate

[0110] 4. γ-ray attenuation coefficient ( 137 Cs, 662 keV): GB / T 11713 - 2015

[0111] Test object: Concrete cylinder (diameter 100 mm, thickness 50 mm).

[0112] Test conditions:

[0113] γ source: 137 Cs radiation source (energy 662 keV, activity 1 mCi).

[0114] Detector: NaI(Tl) scintillation detector

[0115] Test steps:

[0116] Background measurement: Measure the γ photon count rate I0 without the specimen

[0117] Attenuation measurement: Measure the transmitted count rate I after placing the specimen

[0118] Result calculation: Linear attenuation coefficient (d is the thickness of the test piece, unit: cm -1 ).

[0119] 5. Chloride ion diffusion coefficient: GB / T 50082 - 2009

[0120] Test object: Concrete cylinder (diameter 100mm, thickness 50mm).

[0121] Test steps:

[0122] Pretreatment of the test piece: Vacuum saturation water treatment until the mass is constant.

[0123] Electric flux test:

[0124] Place the test piece between 3.0% NaCl solution (cathode) and 0.3mol / L NaOH solution (anode).

[0125] Apply a 60V DC voltage and record the electric flux Q (coulomb) passed within 6h.

[0126] Result calculation:

[0127] Chloride ion diffusion coefficient

[0128] d: Thickness of the test piece (mm), A: Cross - sectional area of the test piece (mm 2 ),

[0129] t: Time (s), z: Cl - Charge number (-1), F: Faraday constant (96485C / mol).

[0130] The test results are shown in Table 3 and Figures 1-4 .

[0131] Table 3 Comparison of concrete properties

[0132]

[0133] From the data in Table 3 above, it can be seen that the concrete of the present invention has the following advantages.

[0134] 1. Significantly improved compressive strength:

[0135] Significantly improved compressive strength

[0136] The compressive strength of Example 2 is 68.5MPa, far exceeding that of Comparative Example 1 (ordinary concrete, 42.3MPa) and Comparative Example 3 (unmodified fiber, 61.2MPa).

[0137] Key factors:

[0138] Modified polypropylene fiber: Modified by plasma treatment and silane coupling agent, the interfacial bonding strength between the fiber and the matrix is improved, and crack propagation is effectively inhibited (compared with Comparative Example 3, the compressive strength is reduced by 11.3%).

[0139] Composite activator (calcium sulfoaluminate clinker + gypsum + LiOH): Activates the active components in steel slag microspheres and promotes the hydration reaction to generate dense C-S-H gel (when there is no activator in Comparative Example 4, the strength drops by 14.1%).

[0140] 2. Lightweight and density optimization

[0141] The dry density of Example 2 is 2150 kg / m 3 , which is 12.2% lower than that of Comparative Example 1 (2450 kg / m 3 ) and 7% lower than that of Comparative Example 5 (ordinary ceramsite, 2310 kg / m 3 ).

[0142] Key factors:

[0143] Industrial waste light aggregate (fly ash ceramsite + steel slag microspheres): Ceramsite provides a lightweight skeleton (bulk density 700 kg / m 3 ), and steel slag microspheres fill the pores (particle size 0.5 - 2 mm), synergistically optimizing the aggregate gradation.

[0144] Classified barite powder: Ultrafine powder (≤10μm accounting for 35%) fills the micropores, reducing the cement dosage (the cement dosage in Example 2 is 250 parts, while that in Comparative Example 1 is 300 parts).

[0145] 3. Good radiation shielding performance

[0146] Neutron shielding rate: In Example 2, it reaches 88.3%, which is 175% higher than that of Comparative Example 1 (32.1%) and 15.4% higher than that of Comparative Example 2 (unclassified barite, 76.5%).

[0147] Technical principle:

[0148] Boron carbide (B4C): Boron element (B) has a high neutron absorption cross-section (~600 b), effectively capturing thermal neutrons.

[0149] Classified barite: Ultrafine powder (≤10μm) and medium-fine powder (10 - 50μm) form a dense packing, reducing the neutron scattering path.

[0150] γ-ray attenuation coefficient: In Example 2, it is 0.38 cm -1 , which is 217% higher than that of Comparative Example 1 (0.12 cm -1 ) and 31% higher than that of Comparative Example 2 (0.29 cm -1 ).

[0151] Core mechanism: The high atomic number of barium sulfate (BaSO4) (Z = 56 for Ba) enhances Compton scattering and the photoelectric effect, and the hierarchical ratio optimizes the uniformity of Ba element distribution.

[0152] 4. Improvement in impermeability and durability

[0153] Chloride ion diffusion coefficient: For Example 2, it is 1.8×10 -12 m 2 / s, much lower than that of Comparative Example 1 (8.9×10 -12 m 2 / s) and Comparative Example 4 (without activator, 3.6×10 -12 m 2 / s).

[0154] Key innovation:

[0155] Nanosilica (mesoporous structure, pore size 3nm): Fills capillary pores and reduces the most probable pore size (mercury intrusion method shows a decrease from 120nm to 35nm).

[0156] Composite activator: Promotes the reaction between CaO and SiO2 in steel slag microspheres, generates more C-S-H gel, and reduces the connected porosity.

[0157] 5. Low-carbon environmental protection and resource recycling

[0158] The utilization rate of industrial waste residue reaches 32% (fly ash ceramsite + steel slag microspheres), and the carbon emission (280kg / m 3 ) is 37.8% lower than that of ordinary concrete (450kg / m 3 ).

[0159] Process optimization:

[0160] Low-temperature calcination of barite (800°C): Saves 35% energy compared with the traditional process (sintering at 1400°C).

[0161] Steam curing replaces high-temperature curing: Reduces energy consumption by 20% - 30%.

[0162] From the above examples, it can be seen that through the three major technical routes of hierarchical activation of barite, modified fiber reinforcement, and synergistic utilization of waste residues, the present invention achieves the following core advantages:

[0163] Synergistic optimization of multiple properties: Simultaneously meets high compressive strength (≥60MPa), light weight (≤2200kg / m 3 ), strong radiation shielding (neutron ≥85%, γ attenuation ≥0.35cm -1 ), and low chloride ion penetration (≤2.5×10 -12 m 2 / s).

[0164] Filling the technological gap: Traditional concrete cannot achieve both radiation shielding and light weight with high strength at the same time. This invention breaks through this contradiction.

[0165] Green and sustainable: The efficient utilization of industrial solid waste and low-temperature processes significantly reduce carbon emissions, meeting the development trend of low-carbon buildings.

[0166] The above are only several limited preferred embodiments of the present invention, and the description is relatively specific and detailed. However, it should not be construed as a limitation to the scope of the patent for the present invention. It should be noted that for those of ordinary skill in the art, without departing from the concept of the present invention, several modifications and improvements can still be made, and these all fall within the protection scope of the present invention.

Claims

1. A hydraulic low-carbon concrete containing barite barium sulfate, characterized in that, It consists of the following raw materials in parts by weight: 200 - 300 parts of 42.5 - grade portland cement, 150 - 250 parts of barium sulfate barite powder, 3 - 8 parts of modified polypropylene fiber, 80 - 120 parts of industrial waste light aggregate, 10 - 20 parts of boron carbide powder, 5 - 15 parts of nano - silica, 2 - 5 parts of polycarboxylate water - reducing agent, 1 - 3 parts of composite activator, and 80 - 120 parts of water; The modified polypropylene fiber is treated by plasma surface treatment and silane coupling agent modification.

2. The hydraulic low-carbon concrete according to claim 1, wherein The barium sulfate barite powder adopts a grading ratio combination: ultrafine powder with a particle size ≤ 10μm accounts for 30% - 40%, fine powder with a particle size of 10 - 30μm accounts for 40% - 50%, medium - fine powder with a particle size of 30 - 50μm accounts for 20% - 30%, and is calcined and activated at 600 - 800°C.

3. The hydraulic low-carbon concrete according to claim 1, characterized in that, The modification treatment steps of the modified polypropylene fiber include: (1) Low - temperature plasma treatment: Under an oxygen atmosphere, treat with a radio - frequency power of 50 - 100W for 5 - 10 minutes; (2) Silane coupling agent treatment: Immerse the plasma - treated fiber in a 1% - 3% KH - 550 ethanol solution and ultrasonically treat at 60°C for 30 - 60 minutes; (3) Heat treatment: Dry and cure at 120 - 150°C for 1 - 2 hours.

4. The hydraulic low-carbon concrete according to claim 1, wherein The industrial waste light aggregate is a composite aggregate of fly ash ceramsite and steel slag microspheres, and the mass ratio of the two is 2:1 - 3:

1. The particle size of the ceramsite is 3 - 8 mm, and the bulk density is 600 - 800 kg / m 3 , and the particle size of the steel slag microspheres is 0.5 - 2 mm.

5. The hydraulic low-carbon concrete according to claim 1, characterized in that, The composite activator is composed of sulfoaluminate clinker, gypsum and lithium hydroxide in a mass ratio of 5:3:1, and the specific surface area is ≥ 450 m 2 / kg.

6. The hydraulic low-carbon concrete according to claim 1, characterized in that, The nano-silica has a mesoporous structure, with a pore diameter of 2 - 5 nm and a specific surface area of 300 - 500 m 2 / g, and its surface is modified by amino silane treatment.

7. The hydraulic low-carbon concrete according to claim 1, wherein , Compressive strength ≥ 60 MPa, dry density ≤ 2200 kg / m 3 , Neutron shielding rate ≥ 85%, 137 γ-ray attenuation coefficient in the case of Cs source ≥ 0.35 cm -1 , Chloride ion diffusion coefficient ≤ 2.5×10 -12 m 2 / s.

8. The preparation method of the hydraulic low-carbon concrete according to any one of claims 1-7, characterized in that, It includes the following steps: (1) Premixing and modification: First, dry - mix 42.5 - grade portland cement, nano - silica, and 1 / 4 - 1 / 2 mass of barium sulfate barite powder for 5 - 10 minutes; (2) Gradient stirring: Add the remaining raw materials in three times, with an interval of 3 - 5 minutes each time; (3) Vibration compaction: Use high - frequency vibration molding at 20 - 40Hz; (4) Steam curing: Cure at a constant temperature of 80 - 90°C for 12 - 24 hours.

9. The preparation method according to claim 8, characterized in that, In step (2), the specific parameters of the gradient stirring are: the stirring speed in the first stage is 60 - 80rpm, and the time is 3min; the stirring speed in the second stage is 120 - 150rpm, and the time is 5min; the stirring speed in the third stage is 60 - 80rpm, and the time is 2min.

10. Application of the hydraulic low - carbon concrete according to any one of claims 1 - 7 in the construction of a nuclear reactor containment, radioactive waste repository, or nuclear medicine protection wall.

Citation Information

Cited By

  • Radiation-proof ultra-high performance recycled concrete and preparation method thereof

    CN120664826A

  • Radiation-proof ultra-high performance recycled concrete and preparation method thereof

    CN120664826B